Polygenic risk for schizophrenia predicting Big Five personality traits in individuals without non-affective psychosis - Lavonius, Veikka; Keltikangas-Järvinen, Liisa; Lyytikäinen, Leo-Pekka; Hamal Mishra, Binisha; Sormunen, Elina; Kähönen, Mika; Raitakari, Olli; Hietala, Jarmo; Lehtimäki, Terho; Saarinen, Aino (ELSEVIER, 2025)
Background: A high genetic risk for schizophrenia, in complex interplay with environmental factors, has been suggested to explain population-level variation in personality traits among individuals who do not develop schizophrenia-spectrum disorders. We investigated, first, whether polygenic risk for schizophrenia (PRSscz) predicts Big Five personality traits in individuals, who have not developed non-affective psychosis. Second, we examined whether any observed associations are specific to PRSscz or evident also for PRS for major depression (PRSDEP).
Study design: The participants came from the population-based, prospective Young Finns Study (n = 1328-1874 in the final analyses). Diagnoses of non-affective psychoses were obtained from the Finnish hospital care register. Personality traits were assessed with the five-factor model including Neuroticism, Conscientiousness, Openness, Agreeableness, and Extraversion. Covariates included age, sex, adulthood educational level, and quality of early family environment (adverse socioeconomic circumstances, unfavorable emotional family atmosphere, and stressful life events).
Results: In those without non-affective psychosis, PRSscz had a positive linear effect on Openness (B = 0.029, 95%CI = 0.006;0.052, p = 0.014) and a quadratic effect on Extraversion (B = -0.018, 95%CI = -0.033;-0.002, p = 0.024), indicating higher levels of Extraversion in those with low/high levels of PRSscz. The PRSscz did not account for other personality traits. The results held after adding covariates or after controlling for PRSDEP. PRSDEP was not associated with any of the personality traits.
Conclusions: Individuals with high PRS for schizophrenia, who have not developed non-affective psychosis, may still develop mildly different personality traits, including higher Openness and lower Extraversion. These findings seem to be specific to PRSscz and are not observed for PRSDEP.